The Effect of Administering Giberelin PGR snd Nasa POC on The Growth of Plant Seedlings Matoa (Pometia pinnata): Pengaruh Pemberian Giberelin PGR dan Nasa POC terhadap Pertumbuhan Bibit Tanaman Matoa (Pometia pinnata) - Suci Lestari; Dwi Fitriani; Fiana Podesta; Suryadi (Universitas Muhammadiyah Sidoarjo, 2026)
This study aimed to determine the interaction between Giberellin Plant Growth Regulator (ZPT) and NASA Liquid Organic Fertilizer (POC) and their effects on the growth of matoa seedlings (Pometia pinnata). This research was conducted in Talang Giring Village, Lubuk Sandi District, Seluma Regency, Bengkulu Province, from April to June, two-factor Randomized Complete Block Design (RCBD) was used. The first factor was Gibberellin ZPT (Z) with four concentration levels: Z0 (control), Z1 (30 ppm), Z2 (60 ppm), and Z3 (90 ppm). The second factor was NASA POC (P) with three concentration levels: P1 (5 ml/l), P2 (7.5 ml/l), and P3 (10 ml/l). There were 12 treatment combinations, replicated 3 times, resulting in a total of 36 experimental units. The observed parameters included plant height, number of leaves, number of roots, and root length. The analysis results indicated that there was no significant interaction between Giberellin ZPT and NASA POC for all observed parameters. The application of Gibberellin ZPT had a significant effect on plant height at 28 days after planting (DAP) and a highly significant effect on the number and length of roots. Meanwhile, the application of NASA POC had a highly significant effect on the number of leaves at 70 DAP and root length.